Solid waste management index for Brazilian Higher Education Institutions. (October 2018) - Moreira, Rodrigo; Malheiros, Tadeu F.; Alfaro, Jose F.; Cetrulo, Tiago B.; Ávila, Lucas V.
Highlights: Higher Education Institutions lack a tool to diagnose and monitor waste management. Indexes are helpful tools to aid decision making. The index presented in this paper distribute its criteria in four main dimensions. The index was applied for three universities in Brazil, and one in the United States. The index was applied and is guaranteed to be able to assess different realities. Abstract: This paper presents the Solid Waste Management Index (SWaMI) for Higher Education Institutions (HEIs). The main objectives are to present how SWaMI was developed, to apply the Index in three different universities in Brazil and one in United States, to statistically compare the results and to present an analysis of these HEIs under the SWaMI assessment dimensions perspective. The SwaMI fills a gap regarding a specific waste management tool for HEIs decision makers, considering the responsibility of educating and training future leaders and the need to insert the sustainable waste management discussion in its end activities. Criteria were selected through literature review and divided in dimensions, further weighted according to their significance in waste management. These weights were discussed and stipulated based on expert opinion using the Budget Allocation Process (BAP) weighting method. The individual indexes for each dimension were further combined into a composite index through the Linear Aggregation Method. Main findings shows that when comparisons were deployed between HEIs, no statistical significance was noticed when the means were compared between universities using ANOVA with Tukey test. Nevertheless, when comparing each dimension within each HEI, there was significant difference between the Policy and Management dimension and the other three dimensions of the evaluation criteria at USP. Researchers concluded that the SWaMI provides decision makers with graphic results concerning HEIs solid waste management situation, hence, it allows the creation of a baseline data on how the current system works, pointing out the dimensions that present the greatest weakness allowing to perform benchmarking between buildings, institutes, and even between HEIs.